Impact of Microfinance Services on Entrepreneurship Development: Empirical Evidence from Pokhara Valley - Karmacharya, Bibek (Kanya Journal, 2023)
Microfinance plays a critical role in consumer entrepreneurship development. This study measures the impact of microfinance services on entrepreneurship development in the Pokhara valley using a sample of 320 individuals. Confirmatory factor analysis (CFA) and structural equation modeling (SEM) are employed to assess the relationship between microfinance services and entrepreneurship development. The CFA results indicate a strong fit, aligning with the hypothesized model. Path analysis reveals significant positive associations between lending services, training and education services, and consultancy services provided by microfinance firms and entrepreneurship development. Conversely, saving services show a negative and insignificant association. These findings underscore the positive impact of certain microfinance services on entrepreneurship development, suggesting the need for policymakers and microfinance company management to prioritize the enhancement of lending, training, and consultancy services while reevaluating the effectiveness of saving services in promoting entrepreneurial endeavors.